Digital Literacy as a Media to Introduce Technology for Elementary School Children - Fauzi, Ahmad; Ridwan, Taufik; Sholihah, Primanita (International Conference on Elementary Education, 2020)
The development of science and technology has changed the world as industry revolution change the world. The industrial revolution 4.0 has changed the economy, employment and even society itself. Educational challenges in the era of the industrial revolution 4.0 in the form of changes in the way of learning, thinking patterns and ways of acting society, especially students in developing creative innovations in various fields. The characteristics that emerge in the 21st century digital world include the academic community must always explore the technological footprint, share in creating ideas and knowledge that will be created, interact and collaborate in social matters by looking at various aspects that will be applied. Primary school-age children must have an understanding in expressing themselves in the field of digital literacy and using media wisely. From the results of research found that children have begun to be familiar with digital devices such as television and gadgets. Not infrequently they also began to get used to spending time in front of these digital devices. This study aims to carry out physical development of motoric, socio-emotional, religious community of young children and elementary school, regarding digital literacy. The result is elementary school children can be directed to be able to think critically, think creatively, collaboratively and communicatively in using Information and Communication Technology